O efeito dos tratamentos térmicos na microestrutura e nas propriedades mecânicas de rodas automotivas fundidas a baixa pressão na liga A356 - Cruz, Daniel Vilela (2019)
The low-pressure die casting process to produce automotive aluminum alloy wheels is well known, and, in the last decades, has been consolidated as the most common way to produce light automotive wheels in large scale. The big competitiveness in this market associated with higher levels of performance required, pushes the companies to seek for process optimizations and cost reduction. In this project, different regions of aluminum alloy wheels, casted in A356 and solidified at different cooling rates, were assessed in terms of its mechanical and microstructural properties in different steps of the manufacturing process, from as casted condition until final painted wheel; the impact of different periods of solution treatment as well as the effects exerted by the painting ovens on these properties were also evaluated. A great reliance was observed between the mechanical properties obtained and the primary and secondary microstructural refinement degrees, similar regions such as the outer and inner flanges of the wheel, cooled at similar rates and, with almost equal refinement degree and SDAS values, have shown practically the same results of elongation and mechanical resistance on all process phases evaluated. Inferior values of elongation and mechanical resistance were found for the wheel spoke, mainly due to its less refined as cast microstructure solidified at lower rates. The solution treatment was found a key process phase in order to transform the Si for the wheels to achieve minimum values of elongation, and the ageing treatment allied with the painting ovens has given the necessary resistance for the product to be applied in the field. The results found delineated a general process panorama and might be used for actual and future manufacturing process optimizations.